A temperature-resistant and salt-resistant polymer microsphere, its preparation method and application
By modifying dendritic mesoporous silica-loaded copper oxide quantum dots, hollow structure polyacrylamide microspheres were prepared by reverse phase emulsion polymerization process, which solved the problem of poor temperature and salt resistance in oil field applications, achieved the stability and controllable expansion of microspheres, and met the efficient demand for oil field oil production.
Patent Information
- Application Number
- CN202411755643.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-03
AI Technical Summary
In oil field applications, existing polymer microspheres have problems such as poor temperature and salt resistance, easy shear crushing and low sealing strength, which are difficult to meet the requirements of water blocking, deep dissection adjustment and displacement in oil field oil production.
Polyacrylamide microspheres with hollow structures were prepared by using modified dendritic mesoporous silica as a carrier and loading copper oxide quantum dots. The process involves modifying dendritic mesoporous silica with a mercaptosilane coupling agent, ultrasonic dispersing of copper oxide quantum dots, and subsequent polymerization under stirring conditions to form microspheres.
The prepared temperature-resistant and salt-resistant polymer microspheres have good stability and can be controlled to expand in brine, which improves the elastic deformation ability of the microspheres and the water absorption and rupture resistance of high-temperature and high-salt environments, and meets the requirements of improving crude oil recovery such as water blocking, deep dissection adjustment and displacement in oil field oil production.
Smart Images

Figure CN119219870B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of petrochemical industry, and particularly relates to a temperature-resistant and salt-resistant polymer microsphere and a preparation method and application thereof. Background Art
[0002] Polymer microspheres have many advantages, such as a variety of synthesis methods, controllable particle size of the synthesized products, good dispersibility, and certain expansion performance and elastic strength. In addition, polymer microspheres are widely used in many aspects. In the field of coatings, adding polymer microspheres to coatings can improve the stain resistance, scrub resistance and color retention of coatings; in the field of biomedicine, microspheres can be used as drug carriers due to their own temperature sensitivity and biodegradability, slowly releasing drugs in the human body, prolonging the half-life of drugs, and keeping the concentration of drugs in the body above the required concentration for a long time. At the same time, microspheres can also protect drugs, especially preventing certain protein drugs from being decomposed by protein enzymes in the body and losing drug activity; in the cosmetics industry, spices, water or oil, as well as functional active substances such as sunscreen, whitening, and freckle removal can be embedded in microspheres to prolong the release time of active substances and increase the durability of cosmetic effects. In addition, microspheres have excellent light scattering properties and can play a whitening role. They can be used as additives in sunscreen cosmetics. In addition, polymer microspheres also have good application effects in other aspects such as leather processing, plastic toughening and conductive polymer modification.
[0003] In addition to the above applications, polymer microspheres have a wider range of applications in the field of oilfield plugging. This type of microspheres is mainly water-absorbent resin microspheres. Due to their large expansion multiples, good toughness and effective delayed expansion performance, they can migrate to the deep formation with the injected water, forming a high-strength plugging of large pores in the formation, so that the subsequent injected water is diverted to areas not affected by the water flow, reducing the water output of the oil well and increasing crude oil production. However, as reservoir conditions become increasingly harsh, conventional chemically cross-linked polymer microspheres have gradually revealed shortcomings such as poor temperature and salt resistance, easy shearing and crushing, and low plugging strength. Therefore, it is particularly important for the oil industry to design and synthesize polymer microspheres with better performance.
[0004] Quantum dots are a new type of semiconductor nanomaterial, a type of semiconductor nanoparticle composed of II-VI or III-V elements with a radius smaller than or close to the exciton Bohr radius. Due to the influence of quantum size effect and dielectric confinement effect, quantum dots have unique properties, which makes quantum dots have great application potential in the fields of oil extraction and catalysis. The prior art generally directly uses quantum dots as tracers or oil displacement agents, and the application range is relatively narrow. CN115306362A directly uses quantum dots as oil displacement agents, and uses the extremely strong penetration and oil washing effects of quantum dots to penetrate into the rock surface to remove the oil film and improve the oil washing efficiency; however, its cost is relatively high, and it does not have the effect of blocking and regulating displacement. CN115181217A prepares core-shell microspheres with fluorescent tracing function, by introducing fluorescent quantum dots in the process of preparing the core microsphere solution, and then mixing and adsorbing with the shell monomer water to prepare the core-shell microsphere solution. The fluorescent quantum dots are located inside the core-shell fluorescent microspheres and will not detach, thereby improving the subsequent detection accuracy. The quantum dot microspheres are prepared into microspheres of ordinary morphology by direct in-situ polymerization process, and only the tracer function of quantum dots is used for detection, and the plugging and flooding effect is limited. The fluorescent microspheres prepared by CN117736722A, CN115247060A, etc. have smooth surfaces and cannot be used as flooding agents. Summary of the invention
[0005] One of the technical problems to be solved by the present invention is the instability and poor expansion of the microsphere system in the prior art. A temperature-resistant and salt-resistant polymer microsphere is provided. The microsphere has good stability and can be controllably expanded in brine, which can meet the on-site operation requirements for improving crude oil recovery such as water plugging, deep profile adjustment and displacement in oil field production.
[0006] The technical solution for achieving the purpose of the present invention is as follows:
[0007] A method for preparing temperature-resistant and salt-resistant polymer microspheres comprises the following steps:
[0008] (1) Modifying dendritic mesoporous silica with a mercaptosilane coupling agent to prepare modified dendritic mesoporous silica;
[0009] (2) adding the modified dendritic mesoporous silica to the copper oxide quantum dot solution, uniformly dispersing by ultrasonication, and obtaining the modified dendritic mesoporous silica loaded with copper oxide quantum dots after centrifugation; the mass ratio of the modified dendritic mesoporous silica to the copper oxide quantum dots is 1:(0.01-0.1);
[0010] (3) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid and a cross-linking agent are added to water respectively, an alkali solution is added to adjust the pH, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0011] (4) adding the modified dendritic mesoporous silica loaded with copper oxide quantum dots, a surfactant, and an azo initiator into an organic solvent, stirring evenly, and passing nitrogen gas to deoxygenate to obtain an oil phase;
[0012] (5) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the reaction is carried out at a temperature of 55-75°C for 1-4 hours to obtain temperature-resistant and salt-resistant polymer microspheres.
[0013] In the previous work (CN118580443A), the inventor used silica of different particle sizes as reinforcing filler and prepared polyacrylamide microspheres by dispersion polymerization, which improved the heat resistance and salt resistance of the microspheres to a certain extent. However, the microspheres are solid structures with large particle sizes, weak heat resistance and salt resistance, poor water absorption and expansion ability, and limited plugging and flooding effects. In order to improve the flooding ability of polyacrylamide microspheres, the present invention uses dendritic mesoporous silica as a carrier and copper oxide quantum dots as an additive to prepare polyacrylamide microspheres with a similar "hollow" structure.
[0014] As an inorganic material, mesoporous materials have many advantages such as large specific surface area, good chemical stability, low synthesis cost, and easy surface modification groups, and are good carriers for quantum dots. The prior art generally uses mesoporous silica as a loading substrate for quantum dots. However, traditional mesoporous silica is a solid structure and has low interfacial bonding ability with the polymer shell. Compared with traditional mesoporous materials, dendritic mesoporous silica has the advantages of unique three-dimensional morphology, open center-radial pores, adjustable particle size, highly accessible internal surface area, high pore capacity, and abundant silicon hydroxyl sites. It has a large number of binding sites with quantum dots, and it itself presents a three-dimensional center-radial porous structure, and the body is relatively loose, which greatly improves the bonding ability between the outer layer of dendritic mesoporous silica and the polymer shell.
[0015] Since the surface of dendritic mesoporous silica has a large number of hydroxyl groups, in order to prevent its agglomeration and improve its loading efficiency for copper oxide quantum dots, the present invention modifies it by a mercaptosilane coupling agent, which reduces the surface energy of the material and improves its dispersibility on the one hand; on the other hand, the mercapto groups in the coupling agent are easy to combine with copper oxide quantum dots, preventing them from being oxidized or agglomerated, and improving the stability of copper oxide quantum dots in solvents. The outermost layer of the modified dendritic mesoporous silica contains a large number of mercapto groups, and is densely arranged, which is not only conducive to combining with copper oxide quantum dots, but also the dense quantum dots attached to the outer layer prevent the quantum dots from further penetrating into the dendritic mesoporous silica, so that the quantum dots are concentratedly loaded on the outer layer of the modified dendritic mesoporous silica, while the inner layer of the modified dendritic mesoporous silica is still a loose dendritic structure.
[0016] The reason why the present invention chooses copper oxide quantum dots is that compared with metallic copper and other metal and its oxide quantum dots, CdTe, ZnS and other quantum dots, there is a spatial restriction between the electron and hole pairs in copper oxide quantum dots, which can generate additional energy, and it is a monoclinic p-type semiconductor with a narrow energy band gap (1.2 eV-1.8 eV), which can effectively adsorb azo initiators, reduce the activation energy required for azo initiators to generate free radicals, and accelerate the decomposition of initiators on the surface of quantum dots. Furthermore, the present invention adopts inverse emulsion polymerization to prepare polymer microspheres, and the water-soluble monomer solution is uniformly dispersed in the oil phase continuous phase through the emulsification of the surfactant, and the polymerization is initiated in the oil-in-water reaction system by the initiator. The presence of the oil-in-water reaction system successfully physically isolates the modified dendritic mesoporous silica from the polymerization monomers, and the densely distributed quantum dots on the outer layer of the modified dendritic mesoporous silica can prevent the azo initiators and polymerization monomers from penetrating into the inner layer of the dendritic mesoporous silica, so that the polymerization of the monomers occurs on the outer surface of the dendritic mesoporous silica, thereby maintaining the loose and porous dendritic structure in the center.
[0017] Furthermore, the specific preparation process of the modified dendritic mesoporous silica is as follows: the dendritic mesoporous silica and the mercaptosilane coupling agent are dispersed in a methanol solution, ammonia water is added, heated and stirred for reaction, and then centrifuged, washed, and dried to obtain the modified dendritic mesoporous silica. The mass volume ratio of the dendritic mesoporous silica and ammonia water is 1g: (0.5-1) mL, the ammonia water concentration is 20wt%; the heating reaction temperature is 55-65°C, and the reaction time is 3-6h.
[0018] Furthermore, in step (1), the mercaptosilane coupling agent is at least one of 3-mercaptopropyltrimethoxysilane and 3-mercaptopropyltriethoxysilane; the particle size of the dendritic mesoporous silica is 50-250nm, and the pore size is 5-25nm. An appropriate amount of mercaptosilane coupling agent not only improves the dispersion performance of the dendritic mesoporous silica, but also increases the loading rate of quantum dots, which is conducive to the formation of a hollow-like structure. The preparation technology of dendritic mesoporous silica is relatively mature. The present invention uses cationic surfactant hexadecyltrimethylammonium bromide and sodium salicylate as structure directing agents, tetraethyl orthosilicate as a silicon source, and triethanolamine as a catalyst in the synthesis process. Dendritic mesoporous silica is synthesized by hydrothermal synthesis.
[0019] Furthermore, in step (1), the mass ratio of the mercaptosilane coupling agent to the dendritic mesoporous silica is (0.1-1): 1. Furthermore, the mass ratio of the mercaptosilane coupling agent to the dendritic mesoporous silica is (0.3-0.6): 1. An appropriate amount of mercaptosilane coupling agent can effectively load quantum dots while avoiding the waste and clogging caused by excessive mercaptosilane coupling agent.
[0020] Furthermore, the copper oxide quantum dot solution in step (2) is a chloroform solution of copper oxide quantum dots.
[0021] Furthermore, in step (2), the ultrasonic power is 100-200 W, and the ultrasonic time is 20-40 min.
[0022] Furthermore, in step (3), the alkali solution is a sodium hydroxide solution or a potassium hydroxide solution, and the pH value is 6-7; and the cross-linking agent is N,N-methylenebisacrylamide.
[0023] Furthermore, in step (4), the surfactant is one or both of Span-80 and Tween-80; the azo initiator is at least one of azobisisobutyronitrile and azobisisoheptylnitrile; and the organic solvent is white oil.
[0024] Furthermore, the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinking agent, surfactant, initiator and modified dendritic mesoporous silica loaded with copper oxide quantum dots is (12-16): (4-8): (0.5-2.5): (1-3): (4-8): (0.05-0.5): 1; the mass ratio of water, organic solvent and modified dendritic mesoporous silica loaded with copper oxide quantum dots is (70-80): (85-100): 1. Furthermore, the reaction temperature of step (5) is 60-70°C. The increase in temperature will accelerate the decomposition rate of the initiator, thereby increasing the number of active centers, accelerating the chain initiation and chain growth, and accelerating the overall reaction rate; however, too high a temperature will cause the polymer degree of polymerization distribution to become wider, the degree of polymerization to decrease, the molecular weight to decrease, and the performance of the polymer microspheres to be affected.
[0025] On the other hand, the present invention also provides a temperature-resistant and salt-resistant polymer microsphere and its application as a profile control and oil displacement agent.
[0026] The polyacrylamide microspheres prepared by the present invention have the characteristics of controllable synthetic particle size, good dispersibility and swelling when in contact with water, etc., and can be directly prepared from the sewage of the oil field to obtain working fluid for injection for profile adjustment, and used in the middle and late stages of oil field development. In the process of injecting polyacrylamide microspheres, the microspheres will first enter the water flow dominant channel, and continuously move forward along the direction of small seepage resistance. When the microspheres enter the pore throats, they will block these pore throats by stacking or bridging, so that the injection pressure is increased, forcing the subsequent injection water to turn to the unaffected oil-containing area, and the injection water flows into the small pores and the area with large seepage resistance, and continuously displaces the crude oil therein. These residual oils will converge into a larger oil flow in the large pores and move toward the oil wellhead, effectively improving the injection water sweep coefficient.
[0027] More importantly, the polyacrylamide microspheres prepared by the present invention have a loose quasi-hollow structure inside, which greatly improves the elastic deformation ability of the microspheres. When the pressure in front of the blocked pore throat increases to a certain value, the polymer microspheres will be easily squeezed and deformed due to the extrusion effect, thereby breaking through the pore throat like an "amoeba". At this time, a certain negative pressure will be formed between the pore throat and the surrounding rocks. The injected water will carry the remaining oil quickly through the small pore throat, and the microspheres will restore their shape after passing through the pore throat and continue to migrate forward.
[0028] The quasi-hollow structure not only improves the elastic deformation ability of the microspheres, but also prevents them from absorbing water and rupturing under high temperature and high salt conditions. After the solid microspheres commonly used in the prior art absorb water and swell, when subjected to external forces, due to the solid structure inside, the inner layer presents extrusion stress, and the outer layer presents expansion tension. The microspheres are prone to stress concentration under different stresses, causing the stress in the local area to exceed its bearing capacity, leading to rupture. The hollow-structured polyacrylamide microspheres have a loose hollow structure inside, and the loose structure inside can effectively absorb and disperse the expansion tension on the surface layer, preventing the microspheres from rupturing. The microspheres have good stability and can expand controllably in salt water, meeting the requirements of on-site operations such as water plugging, deep profile adjustment and displacement in oil field production to improve crude oil recovery.
[0029] Compared with the existing disclosed technology, the positive effects of the present invention are:
[0030] (1) Compared with the prior art method of preparing hollow microspheres by calcining or corroding to remove the central template, the hollow-structured polyacrylamide microspheres prepared by the present invention have a simple process, are easy to operate, and are conducive to industrial large-scale production.
[0031] (2) The presence of the oil-in-water reaction system successfully physically isolates the modified dendritic mesoporous silica from the polymerized monomers. In addition, the quantum dots concentrated on the outer layer of the modified dendritic mesoporous silica can prevent the azo initiators and polymerized monomers from penetrating into the inner layer of the dendritic mesoporous silica, allowing the polymerization of the monomers to occur on the outer surface of the dendritic mesoporous silica, thereby maintaining the loose and porous dendritic structure in the center.
[0032] (3) The polyacrylamide microspheres prepared by the present invention have a loose quasi-hollow structure inside, which not only improves the elastic deformation ability of the microspheres, but also prevents them from absorbing water and rupturing under high temperature and high salt conditions.
[0033] (4) The microspheres have good stability and can expand controllably in brine, which can meet the requirements of on-site operations such as water plugging, deep profile adjustment and displacement in oil field production to enhance crude oil recovery. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1This is a transmission electron micrograph of the temperature-resistant and salt-resistant polymer microspheres prepared in Example 10;
[0035] Figure 2 This is a transmission electron microscopy image of the temperature-resistant and salt-resistant polymer microspheres prepared in Comparative Example 1;
[0036] Figure 3 This is a transmission electron micrograph of the temperature-resistant and salt-resistant polymer microspheres prepared in Comparative Example 2. DETAILED DESCRIPTION
[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items. The present invention will be further described below in conjunction with specific embodiments so that those skilled in the art can better understand the present invention and can implement it, but the embodiments are not intended to limit the present invention.
[0038] Example 1
[0039] A method for preparing temperature-resistant and salt-resistant polymer microspheres comprises the following steps:
[0040] (1) Dispersing dendritic mesoporous silica and mercaptosilane coupling agent in methanol solution, adding ammonia water, heating and stirring to react, and then centrifuging, washing, and drying to obtain modified dendritic mesoporous silica; wherein the mass volume ratio of dendritic mesoporous silica and ammonia water is 1g:0.8mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 55°C, and the reaction time is 6h; the mercaptosilane coupling agent is 3-mercaptopropyltrimethoxysilane; the average particle size of the dendritic mesoporous silica is 150nm, and the average pore size is 12nm; the mass ratio of the mercaptosilane coupling agent to the dendritic mesoporous silica is 0.3:1;
[0041] (2) adding the modified dendritic mesoporous silica to a chloroform solution of copper oxide quantum dots having an average particle size of 5 nm, uniformly dispersing the solution by ultrasonication, and obtaining the modified dendritic mesoporous silica loaded with copper oxide quantum dots after centrifugation; the mass ratio of the modified dendritic mesoporous silica to the copper oxide quantum dots is 1:0.01; the ultrasonic power is 100 W, and the ultrasonic time is 40 min;
[0042] (3) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, and a cross-linking agent N,N-methylenebisacrylamide are added to water, the pH is adjusted to 6 by adding sodium hydroxide solution, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0043] (4) Adding the modified dendritic mesoporous silica loaded with copper oxide quantum dots, a surfactant, and an azo initiator azobisisobutyronitrile into an organic solvent white oil, stirring evenly, and passing nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 3:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinking agent, surfactant, initiator, and the modified dendritic mesoporous silica loaded with copper oxide quantum dots is 12:4:0.5:1:4:0.05:1; the mass ratio of water, organic solvent, and the modified dendritic mesoporous silica loaded with copper oxide quantum dots is 70:85:1;
[0044] (5) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the mixture is reacted at 60°C for 4 hours to obtain temperature-resistant and salt-resistant polymer microspheres.
[0045] Example 2
[0046] A method for preparing temperature-resistant and salt-resistant polymer microspheres comprises the following steps:
[0047] (1) Dispersing dendritic mesoporous silica and mercaptosilane coupling agent in methanol solution, adding ammonia water, heating and stirring to react, and then centrifuging, washing, and drying to obtain modified dendritic mesoporous silica; wherein the mass volume ratio of dendritic mesoporous silica and ammonia water is 1g:0.8mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 65°C, and the reaction time is 3h; the mercaptosilane coupling agent is 3-mercaptopropyltriethoxysilane; the average particle size of the dendritic mesoporous silica is 150nm, and the average pore size is 12nm; the mass ratio of the mercaptosilane coupling agent to the dendritic mesoporous silica is 0.6:1;
[0048] (2) adding the modified dendritic mesoporous silica to a chloroform solution of copper oxide quantum dots having an average particle size of 5 nm, uniformly dispersing the solution by ultrasonication, and obtaining the modified dendritic mesoporous silica loaded with copper oxide quantum dots after centrifugation; the mass ratio of the modified dendritic mesoporous silica to the copper oxide quantum dots is 1:0.1; the ultrasonic power is 200 W, and the ultrasonic time is 20 min;
[0049] (3) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, and a cross-linking agent N,N-methylenebisacrylamide are added to water respectively, sodium hydroxide solution is added to adjust the pH to 7, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0050] (4) Adding the modified dendritic mesoporous silica loaded with copper oxide quantum dots, a surfactant, and an azo initiator azobisisobutyronitrile into an organic solvent white oil, stirring evenly, and passing nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 3:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinking agent, surfactant, initiator, and the modified dendritic mesoporous silica loaded with copper oxide quantum dots is 16:8:2.5:3:8:0.5:1; the mass ratio of water, organic solvent, and the modified dendritic mesoporous silica loaded with copper oxide quantum dots is 80:100:1;
[0051] (5) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the mixture is reacted at 70°C for 1 hour to obtain temperature-resistant and salt-resistant polymer microspheres.
[0052] Example 3
[0053] A method for preparing temperature-resistant and salt-resistant polymer microspheres comprises the following steps:
[0054] (1) Dispersing dendritic mesoporous silica and mercaptosilane coupling agent in methanol solution, adding ammonia water, heating and stirring to react, and then centrifuging, washing, and drying to obtain modified dendritic mesoporous silica; wherein the mass volume ratio of dendritic mesoporous silica and ammonia water is 1g:0.8mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 65°C, and the reaction time is 6h; the mercaptosilane coupling agent is 3-mercaptopropyltrimethoxysilane; the average particle size of the dendritic mesoporous silica is 150nm, and the average pore size is 12nm; the mass ratio of the mercaptosilane coupling agent to the dendritic mesoporous silica is 0.3:1;
[0055] (2) adding the modified dendritic mesoporous silica to a chloroform solution of copper oxide quantum dots having an average particle size of 5 nm, uniformly dispersing the solution by ultrasonication, and obtaining the modified dendritic mesoporous silica loaded with copper oxide quantum dots after centrifugation; the mass ratio of the modified dendritic mesoporous silica to the copper oxide quantum dots is 1:0.1; the ultrasonic power is 100 W, and the ultrasonic time is 40 min;
[0056] (3) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, and a cross-linking agent N,N-methylenebisacrylamide are added to water respectively, sodium hydroxide solution is added to adjust the pH to 7, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0057] (4) Add the modified dendritic mesoporous silica loaded with copper oxide quantum dots, surfactant, and azo initiator azobisisobutyronitrile into the organic solvent white oil, stir evenly, and pass nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 3:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinking agent, surfactant, initiator, and modified dendritic mesoporous silica loaded with copper oxide quantum dots is 12:8:2.5:1:4:0.5:1; the mass ratio of water, organic solvent, and modified dendritic mesoporous silica loaded with copper oxide quantum dots is 70:100:1;
[0058] (5) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the mixture is reacted at 70°C for 4 hours to obtain temperature-resistant and salt-resistant polymer microspheres.
[0059] Example 4
[0060] A method for preparing temperature-resistant and salt-resistant polymer microspheres comprises the following steps:
[0061] (1) Dispersing dendritic mesoporous silica and mercaptosilane coupling agent in methanol solution, adding ammonia water, heating and stirring to react, and then centrifuging, washing, and drying to obtain modified dendritic mesoporous silica; wherein the mass volume ratio of dendritic mesoporous silica and ammonia water is 1g:0.8mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 58°C, and the reaction time is 4h; the mercaptosilane coupling agent is 3-mercaptopropyltrimethoxysilane; the average particle size of the dendritic mesoporous silica is 150nm, and the average pore size is 12nm; the mass ratio of the mercaptosilane coupling agent to the dendritic mesoporous silica is 0.4:1;
[0062] (2) adding the modified dendritic mesoporous silica to a chloroform solution of copper oxide quantum dots having an average particle size of 5 nm, uniformly dispersing the solution by ultrasonication, and obtaining the modified dendritic mesoporous silica loaded with copper oxide quantum dots after centrifugation; the mass ratio of the modified dendritic mesoporous silica to the copper oxide quantum dots is 1:0.03; the ultrasonic power is 130 W, and the ultrasonic time is 30 min;
[0063] (3) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, and a cross-linking agent N,N-methylenebisacrylamide are added to water, the pH is adjusted to 6 by adding sodium hydroxide solution, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0064] (4) Adding the modified dendritic mesoporous silica loaded with copper oxide quantum dots, a surfactant, and an azo initiator azobisisobutyronitrile into an organic solvent white oil, stirring evenly, and passing nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 3:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinking agent, surfactant, initiator, and the modified dendritic mesoporous silica loaded with copper oxide quantum dots is 13:5:1:1.5:5:0.1:1; the mass ratio of water, organic solvent, and the modified dendritic mesoporous silica loaded with copper oxide quantum dots is 75:90:1;
[0065] (5) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the mixture is reacted at 62°C for 3 hours to obtain temperature-resistant and salt-resistant polymer microspheres.
[0066] Example 5
[0067] A method for preparing temperature-resistant and salt-resistant polymer microspheres comprises the following steps:
[0068] (1) Dispersing dendritic mesoporous silica and mercaptosilane coupling agent in methanol solution, adding ammonia water, heating and stirring to react, and then centrifuging, washing, and drying to obtain modified dendritic mesoporous silica; wherein the mass volume ratio of dendritic mesoporous silica and ammonia water is 1g:0.8mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 62°C, and the reaction time is 4h; the mercaptosilane coupling agent is 3-mercaptopropyltriethoxysilane; the average particle size of the dendritic mesoporous silica is 150nm, and the average pore size is 12nm; the mass ratio of the mercaptosilane coupling agent to the dendritic mesoporous silica is 0.5:1;
[0069] (2) adding the modified dendritic mesoporous silica to a chloroform solution of copper oxide quantum dots having an average particle size of 5 nm, uniformly dispersing the solution by ultrasonication, and obtaining the modified dendritic mesoporous silica loaded with copper oxide quantum dots after centrifugation; the mass ratio of the modified dendritic mesoporous silica to the copper oxide quantum dots is 1:0.08; the ultrasonic power is 180 W, and the ultrasonic time is 25 min;
[0070] (3) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, and a cross-linking agent N,N-methylenebisacrylamide are added to water respectively, sodium hydroxide solution is added to adjust the pH to 7, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0071] (4) Add the modified dendritic mesoporous silica loaded with copper oxide quantum dots, surfactant, and azo initiator azobisisobutyronitrile into the organic solvent white oil, stir evenly, and pass nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 3:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinking agent, surfactant, initiator, and modified dendritic mesoporous silica loaded with copper oxide quantum dots is 15:7:2:2.5:7:0.3:1; the mass ratio of water, organic solvent, and modified dendritic mesoporous silica loaded with copper oxide quantum dots is 78:95:1;
[0072] (5) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the mixture is reacted at 68°C for 2 h to obtain temperature-resistant and salt-resistant polymer microspheres.
[0073] Example 6
[0074] A method for preparing temperature-resistant and salt-resistant polymer microspheres comprises the following steps:
[0075] (1) Dispersing dendritic mesoporous silica and mercaptosilane coupling agent in methanol solution, adding ammonia water, heating and stirring to react, and then centrifuging, washing, and drying to obtain modified dendritic mesoporous silica; wherein the mass volume ratio of dendritic mesoporous silica and ammonia water is 1g:0.8mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 60°C, and the reaction time is 4h; the mercaptosilane coupling agent is 3-mercaptopropyltrimethoxysilane; the average particle size of the dendritic mesoporous silica is 150nm, and the average pore size is 12nm; the mass ratio of the mercaptosilane coupling agent to the dendritic mesoporous silica is 0.1:1;
[0076] (2) adding the modified dendritic mesoporous silica to a chloroform solution of copper oxide quantum dots having an average particle size of 5 nm, uniformly dispersing the solution by ultrasonication, and obtaining the modified dendritic mesoporous silica loaded with copper oxide quantum dots after centrifugation; the mass ratio of the modified dendritic mesoporous silica to the copper oxide quantum dots is 1:0.06; the ultrasonic power is 150 W, and the ultrasonic time is 30 min;
[0077] (3) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, and a cross-linking agent N,N-methylenebisacrylamide are added to water respectively, sodium hydroxide solution is added to adjust the pH to 7, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0078] (4) Add the modified dendritic mesoporous silica loaded with copper oxide quantum dots, surfactant, and azo initiator azobisisobutyronitrile into the organic solvent white oil, stir evenly, and pass nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 3:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinking agent, surfactant, initiator, and modified dendritic mesoporous silica loaded with copper oxide quantum dots is 14:6:1.5:2:6:0.2:1; the mass ratio of water, organic solvent, and modified dendritic mesoporous silica loaded with copper oxide quantum dots is 75:95:1;
[0079] (5) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the mixture is reacted at 65°C for 3 hours to obtain temperature-resistant and salt-resistant polymer microspheres.
[0080] Example 7
[0081] A method for preparing temperature-resistant and salt-resistant polymer microspheres comprises the following steps:
[0082] (1) Dispersing dendritic mesoporous silica and mercaptosilane coupling agent in methanol solution, adding ammonia water, heating and stirring to react, and then centrifuging, washing, and drying to obtain modified dendritic mesoporous silica; wherein the mass volume ratio of dendritic mesoporous silica and ammonia water is 1g:0.8mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 60°C, and the reaction time is 4h; the mercaptosilane coupling agent is 3-mercaptopropyltrimethoxysilane; the average particle size of the dendritic mesoporous silica is 150nm, and the average pore size is 12nm; the mass ratio of the mercaptosilane coupling agent to the dendritic mesoporous silica is 1:1;
[0083] (2) adding the modified dendritic mesoporous silica to a chloroform solution of copper oxide quantum dots having an average particle size of 5 nm, uniformly dispersing the solution by ultrasonication, and obtaining the modified dendritic mesoporous silica loaded with copper oxide quantum dots after centrifugation; the mass ratio of the modified dendritic mesoporous silica to the copper oxide quantum dots is 1:0.06; the ultrasonic power is 150 W, and the ultrasonic time is 30 min;
[0084] (3) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, and a cross-linking agent N,N-methylenebisacrylamide are added to water respectively, sodium hydroxide solution is added to adjust the pH to 7, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0085] (4) Add the modified dendritic mesoporous silica loaded with copper oxide quantum dots, surfactant, and azo initiator azobisisobutyronitrile into the organic solvent white oil, stir evenly, and pass nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 3:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinking agent, surfactant, initiator, and modified dendritic mesoporous silica loaded with copper oxide quantum dots is 14:6:1.5:2:6:0.2:1; the mass ratio of water, organic solvent, and modified dendritic mesoporous silica loaded with copper oxide quantum dots is 75:95:1;
[0086] (5) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the mixture is reacted at 65°C for 3 hours to obtain temperature-resistant and salt-resistant polymer microspheres.
[0087] Example 8
[0088] A method for preparing temperature-resistant and salt-resistant polymer microspheres comprises the following steps:
[0089] (1) Dispersing dendritic mesoporous silica and mercaptosilane coupling agent in methanol solution, adding ammonia water, heating and stirring to react, and then centrifuging, washing, and drying to obtain modified dendritic mesoporous silica; wherein the mass volume ratio of dendritic mesoporous silica and ammonia water is 1g:0.8mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 60°C, and the reaction time is 4h; the mercaptosilane coupling agent is 3-mercaptopropyltrimethoxysilane; the average particle size of the dendritic mesoporous silica is 150nm, and the average pore size is 12nm; the mass ratio of the mercaptosilane coupling agent to the dendritic mesoporous silica is 0.4:1;
[0090] (2) adding the modified dendritic mesoporous silica to a chloroform solution of copper oxide quantum dots having an average particle size of 5 nm, uniformly dispersing the solution by ultrasonication, and obtaining the modified dendritic mesoporous silica loaded with copper oxide quantum dots after centrifugation; the mass ratio of the modified dendritic mesoporous silica to the copper oxide quantum dots is 1:0.06; the ultrasonic power is 150 W, and the ultrasonic time is 30 min;
[0091] (3) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, and a cross-linking agent N,N-methylenebisacrylamide are added to water respectively, sodium hydroxide solution is added to adjust the pH to 7, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0092] (4) Add the modified dendritic mesoporous silica loaded with copper oxide quantum dots, surfactant, and azo initiator azobisisobutyronitrile into the organic solvent white oil, stir evenly, and pass nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 3:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinking agent, surfactant, initiator, and modified dendritic mesoporous silica loaded with copper oxide quantum dots is 14:6:1.5:2:6:0.2:1; the mass ratio of water, organic solvent, and modified dendritic mesoporous silica loaded with copper oxide quantum dots is 75:95:1;
[0093] (5) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the mixture is reacted at 55°C for 3 hours to obtain temperature-resistant and salt-resistant polymer microspheres.
[0094] Example 9
[0095] A method for preparing temperature-resistant and salt-resistant polymer microspheres comprises the following steps:
[0096] (1) Dispersing dendritic mesoporous silica and mercaptosilane coupling agent in methanol solution, adding ammonia water, heating and stirring to react, and then centrifuging, washing, and drying to obtain modified dendritic mesoporous silica; wherein the mass volume ratio of dendritic mesoporous silica and ammonia water is 1g:0.8mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 60°C, and the reaction time is 4h; the mercaptosilane coupling agent is 3-mercaptopropyltrimethoxysilane; the average particle size of the dendritic mesoporous silica is 150nm, and the average pore size is 12nm; the mass ratio of the mercaptosilane coupling agent to the dendritic mesoporous silica is 0.4:1;
[0097] (2) adding the modified dendritic mesoporous silica to a chloroform solution of copper oxide quantum dots having an average particle size of 5 nm, uniformly dispersing the solution by ultrasonication, and obtaining the modified dendritic mesoporous silica loaded with copper oxide quantum dots after centrifugation; the mass ratio of the modified dendritic mesoporous silica to the copper oxide quantum dots is 1:0.06; the ultrasonic power is 150 W, and the ultrasonic time is 30 min;
[0098] (3) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, and a cross-linking agent N,N-methylenebisacrylamide are added to water respectively, sodium hydroxide solution is added to adjust the pH to 7, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0099] (4) Add the modified dendritic mesoporous silica loaded with copper oxide quantum dots, surfactant, and azo initiator azobisisobutyronitrile into the organic solvent white oil, stir evenly, and pass nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 3:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinking agent, surfactant, initiator, and modified dendritic mesoporous silica loaded with copper oxide quantum dots is 14:6:1.5:2:6:0.2:1; the mass ratio of water, organic solvent, and modified dendritic mesoporous silica loaded with copper oxide quantum dots is 75:95:1;
[0100] (5) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the mixture is reacted at 75°C for 3 hours to obtain temperature-resistant and salt-resistant polymer microspheres.
[0101] Example 10
[0102] A method for preparing temperature-resistant and salt-resistant polymer microspheres comprises the following steps:
[0103] (1) Dispersing dendritic mesoporous silica and mercaptosilane coupling agent in methanol solution, adding ammonia water, heating and stirring to react, and then centrifuging, washing, and drying to obtain modified dendritic mesoporous silica; wherein the mass volume ratio of dendritic mesoporous silica and ammonia water is 1g:0.8mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 60°C, and the reaction time is 4h; the mercaptosilane coupling agent is 3-mercaptopropyltrimethoxysilane; the average particle size of the dendritic mesoporous silica is 150nm, and the average pore size is 12nm; the mass ratio of the mercaptosilane coupling agent to the dendritic mesoporous silica is 0.4:1;
[0104] (2) adding the modified dendritic mesoporous silica to a chloroform solution of copper oxide quantum dots having an average particle size of 5 nm, uniformly dispersing the solution by ultrasonication, and obtaining the modified dendritic mesoporous silica loaded with copper oxide quantum dots after centrifugation; the mass ratio of the modified dendritic mesoporous silica to the copper oxide quantum dots is 1:0.06; the ultrasonic power is 150 W, and the ultrasonic time is 30 min;
[0105] (3) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, and a cross-linking agent N,N-methylenebisacrylamide are added to water respectively, sodium hydroxide solution is added to adjust the pH to 7, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0106] (4) Add the modified dendritic mesoporous silica loaded with copper oxide quantum dots, surfactant, and azo initiator azobisisobutyronitrile into the organic solvent white oil, stir evenly, and pass nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 3:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinking agent, surfactant, initiator, and modified dendritic mesoporous silica loaded with copper oxide quantum dots is 14:6:1.5:2:6:0.2:1; the mass ratio of water, organic solvent, and modified dendritic mesoporous silica loaded with copper oxide quantum dots is 75:95:1;
[0107] (5) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the mixture is reacted at 65°C for 3 hours to obtain temperature-resistant and salt-resistant polymer microspheres.
[0108] Comparative Example 1
[0109] A method for preparing temperature-resistant and salt-resistant polymer microspheres comprises the following steps:
[0110] (1) Dispersing dendritic mesoporous silica and mercaptosilane coupling agent in methanol solution, adding ammonia water, heating and stirring to react, and then centrifuging, washing, and drying to obtain modified dendritic mesoporous silica; wherein the mass volume ratio of dendritic mesoporous silica and ammonia water is 1g:0.8mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 60°C, and the reaction time is 4h; the mercaptosilane coupling agent is 3-mercaptopropyltrimethoxysilane; the average particle size of the dendritic mesoporous silica is 150nm, and the average pore size is 12nm; the mass ratio of the mercaptosilane coupling agent to the dendritic mesoporous silica is 0.4:1;
[0111] (2) adding the modified dendritic mesoporous silica to a chloroform solution of copper oxide quantum dots having an average particle size of 5 nm, uniformly dispersing the solution by ultrasonication, and obtaining the modified dendritic mesoporous silica loaded with copper oxide quantum dots after centrifugation; the mass ratio of the modified dendritic mesoporous silica to the copper oxide quantum dots is 1:0.06; the ultrasonic power is 150 W, and the ultrasonic time is 30 min;
[0112] (3) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, a crosslinking agent N,N-methylenebisacrylamide, and an azo initiator azobisisobutyronitrile are added to water, and sodium hydroxide solution is added to adjust the pH to 7, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0113] (4) Adding the modified dendritic mesoporous silica loaded with copper oxide quantum dots and a surfactant to an organic solvent white oil, stirring evenly, and passing nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 3:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinking agent, surfactant, initiator and the modified dendritic mesoporous silica loaded with copper oxide quantum dots is 14:6:1.5:2:6:0.2:1; the mass ratio of water, organic solvent and the modified dendritic mesoporous silica loaded with copper oxide quantum dots is 75:95:1;
[0114] (5) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the mixture is reacted at 65°C for 3 hours to obtain temperature-resistant and salt-resistant polymer microspheres.
[0115] Comparative Example 2
[0116] A method for preparing temperature-resistant and salt-resistant polymer microspheres comprises the following steps:
[0117] (1) Dispersing dendritic mesoporous silica and mercaptosilane coupling agent in methanol solution, adding ammonia water, heating and stirring to react, and then centrifuging, washing, and drying to obtain modified dendritic mesoporous silica; wherein the mass volume ratio of dendritic mesoporous silica and ammonia water is 1g:0.8mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 60°C, and the reaction time is 4h; the mercaptosilane coupling agent is 3-mercaptopropyltrimethoxysilane; the average particle size of the dendritic mesoporous silica is 150nm, and the average pore size is 12nm; the mass ratio of the mercaptosilane coupling agent to the dendritic mesoporous silica is 0.4:1;
[0118] (2) adding the modified dendritic mesoporous silica to a chloroform solution of copper oxide quantum dots having an average particle size of 5 nm, uniformly dispersing the solution by ultrasonication, and obtaining the modified dendritic mesoporous silica loaded with copper oxide quantum dots after centrifugation; the mass ratio of the modified dendritic mesoporous silica to the copper oxide quantum dots is 1:0; the ultrasonic power is 150 W, and the ultrasonic time is 30 min;
[0119] (3) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, and a cross-linking agent N,N-methylenebisacrylamide are added to water respectively, sodium hydroxide solution is added to adjust the pH to 7, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0120] (4) Add the modified dendritic mesoporous silica loaded with copper oxide quantum dots, surfactant, and azo initiator azobisisobutyronitrile into the organic solvent white oil, stir evenly, and pass nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 3:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinking agent, surfactant, initiator, and modified dendritic mesoporous silica loaded with copper oxide quantum dots is 14:6:1.5:2:6:0.2:1; the mass ratio of water, organic solvent, and modified dendritic mesoporous silica loaded with copper oxide quantum dots is 75:95:1;
[0121] (5) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the mixture is reacted at 65°C for 3 hours to obtain temperature-resistant and salt-resistant polymer microspheres.
[0122] Performance test: The heat-resistant and salt-resistant polymer microspheres prepared in Examples 1-10 and Comparative Examples 1-2 were dispersed in simulated formation water with a mineralization of 30,000 mg / L, expanded at 80°C for different times, and the expansion multiples were measured. The results are shown in Table 1.
[0123] Low permeability cores were selected for evaluation of oil displacement effect: first, the cores were saturated with simulated formation water to determine their pore volume; then, the cores were saturated with simulated crude oil; the cores were displaced with simulated formation water until the outlet end stopped producing oil, and the recovery factor A was determined; a dispersion of temperature-resistant and salt-resistant polymer microspheres was injected into the cores and placed at 65°C for 5 days; the cores were displaced with simulated formation water again until the outlet end stopped producing oil, and the recovery factor B was determined; the recovery factor increase was C (%) = (BA) / AX 100%, and the results are shown in Table 1.
[0124]
[0125] Depend on Figure 1It can be seen that the present invention prepares hollow-structured polyacrylamide microspheres with a smaller particle size: the outermost layer of the modified dendritic mesoporous silica contains a large number of thiol groups and is densely arranged, which is not only conducive to combining with copper oxide quantum dots, but also the quantum dots preferentially attached to the outer layer prevent the quantum dots from further penetrating into the dendritic mesoporous silica, so that the quantum dots are concentratedly loaded on the outer layer of the modified dendritic mesoporous silica, while the inner layer of the modified dendritic mesoporous silica is still a loose dendritic structure; and the quantum dots concentratedly distributed on the outer layer of the modified dendritic mesoporous silica can prevent azo initiators and polymerization monomers from penetrating into the inner layer of the dendritic mesoporous silica, so that the polymerization of the monomers occurs on the outer surface of the dendritic mesoporous silica, thereby maintaining the loose and porous dendritic structure in the center, while the shell layer is a dense polyacrylamide polymer. At the same time, due to the open central-radial pore structure of dendritic mesoporous silica, the density of the central part of the dendritic mesoporous silica is higher than that of the outer layer, and the inhomogeneity of the copper oxide quantum dot catalysis leads to an irregular hollow structure. Figure 1 It can also be seen that the internal hollow morphology formed by the microspheres is irregular. This further illustrates that, compared with other types of quantum dots, there is a spatial restriction between the electron and hole pairs in copper oxide quantum dots, which can generate additional energy. Moreover, copper oxide quantum dots are monoclinic p-type semiconductors with a narrow energy band gap (1.2 eV -1.8 eV), which can effectively adsorb azo initiators, reduce the activation energy required for azo initiators to generate free radicals, and prevent initiators from entering the inner layer of dendritic mesoporous silica, thereby forming a quasi-hollow structure.
[0126] It can also be seen from the data in Table 1 that the polyacrylamide microspheres with a quasi-hollow structure prepared by the present invention greatly improve the elastic deformation ability of the microspheres. The injected water will carry the remaining oil quickly through the small pore throats. After passing through the pore throats, the microspheres will restore their shape and continue to move forward, thereby improving the plugging rate and oil recovery rate. The quasi-hollow structure not only improves the elastic deformation ability of the microspheres, but also prevents them from absorbing water and breaking under high temperature and high salt conditions.
[0127] Depend on Figure 2 It can be seen that in Comparative Example 1, the modified dendritic mesoporous silica loaded with copper oxide quantum dots and the azo initiator azobisisobutyronitrile were not mixed in advance, which would cause polar molecules such as acrylamide and acrylic acid monomers, N,N-methylenebisacrylamide crosslinking agents to combine with the copper oxide quantum dots in advance, and the copper oxide quantum dots could not play a role in adsorbing and blocking the initiator, and could not form a hollow structure, and the microsphere particle size was too large. Figure 3As shown in Comparative Example 2, when the mass ratio of modified dendritic mesoporous silica and copper oxide quantum dots is 1:0, that is, copper oxide quantum dots are not added, a quantum dot barrier layer cannot be formed on the surface of the dendritic mesoporous silica, allowing the initiator and the polymerization monomer to enter the inner layer of the dendritic mesoporous silica, resulting in polymerization of monomers in the inner layer of the dendritic mesoporous silica, which is not conducive to the formation of a hollow structure-like structure.
[0128] In summary, the present invention prepares heat-resistant and salt-resistant polymer microspheres with a hollow structure through an inverse emulsion polymerization process. The microspheres have good stability and can expand controllably in brine, and can meet the on-site operation requirements for improving crude oil recovery such as water plugging, deep profile adjustment and displacement in oil field production.
[0129] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing temperature-resistant and salt-resistant polymer microspheres, characterized in that: The following steps are involved: (1) Modifying dendritic mesoporous silica with a mercaptosilane coupling agent to prepare modified dendritic mesoporous silica; wherein cationic surfactants hexadecyltrimethylammonium bromide and sodium salicylate are used as structure directing agents, tetraethyl orthosilicate is used as a silicon source, and triethanolamine is used as a catalyst in the synthesis process, and the dendritic mesoporous silica is synthesized by a hydrothermal synthesis method; the particle size of the dendritic mesoporous silica is 50-250 nm, and the pore size is 5-25 nm; (2) adding the modified dendritic mesoporous silica to the copper oxide quantum dot solution, uniformly dispersing by ultrasonication, and obtaining the modified dendritic mesoporous silica loaded with copper oxide quantum dots after centrifugation; the mass ratio of the modified dendritic mesoporous silica to the copper oxide quantum dots is 1:(0.01-0.1); (3) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid and a cross-linking agent are added to water respectively, an alkali solution is added to adjust the pH, and nitrogen is passed to deoxygenate to obtain an aqueous phase; (4) adding the modified dendritic mesoporous silica loaded with copper oxide quantum dots, a surfactant, and an azo initiator into an organic solvent, stirring evenly, and passing nitrogen gas to deoxygenate to obtain an oil phase; (5) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the reaction is carried out at a temperature of 55-75°C for 1-4 hours to obtain temperature-resistant and salt-resistant polymer microspheres.
2. The method for preparing the temperature-resistant and salt-resistant polymer microspheres according to claim 1, characterized in that: In step (1), the mercaptosilane coupling agent is at least one of 3-mercaptopropyltrimethoxysilane and 3-mercaptopropyltriethoxysilane.
3. The method for preparing the temperature-resistant and salt-resistant polymer microspheres according to claim 1, characterized in that: In step (1), the mass ratio of the mercaptosilane coupling agent to the dendritic mesoporous silica is (0.1-1):
1.
4. The method for preparing the temperature-resistant and salt-resistant polymer microspheres according to claim 1, characterized in that: The copper oxide quantum dot solution in step (2) is a chloroform solution of copper oxide quantum dots.
5. The method for preparing the temperature-resistant and salt-resistant polymer microspheres according to claim 1, characterized in that: In step (2), the ultrasonic power is 100-200 W, and the ultrasonic time is 20-40 min.
6. The method for preparing the temperature-resistant and salt-resistant polymer microspheres according to claim 1, characterized in that: In step (3), the alkali solution is a sodium hydroxide solution or a potassium hydroxide solution with a pH of 6-7; and the cross-linking agent is N,N-methylenebisacrylamide.
7. The method for preparing the temperature-resistant and salt-resistant polymer microspheres according to claim 1, characterized in that: In step (4), the surfactant is one or both of Span-80 and Tween-80; the azo initiator is at least one of azobisisobutyronitrile and azobisisoheptanenitrile; and the organic solvent is white oil.
8. The method for preparing the temperature-resistant and salt-resistant polymer microspheres according to claim 1, characterized in that: The mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinker, surfactant, initiator and modified dendritic mesoporous silica loaded with copper oxide quantum dots is (12-16): (4-8): (0.5-2.5): (1-3): (4-8): (0.05-0.5): 1; the mass ratio of water, organic solvent and modified dendritic mesoporous silica loaded with copper oxide quantum dots is (70-80): (85-100):
1.
9. A heat-resistant and salt-resistant polymer microsphere, characterized in that: The microspheres are prepared by the method for preparing the heat-resistant and salt-resistant polymer microspheres according to any one of claims 1 to 8.
10. Use of the temperature-resistant and salt-resistant polymer microspheres as claimed in claim 9 as a profile control and oil displacement agent.
Citation Information
Patent Citations
Preparation method of core-shell type fluorescent microsphere profile control and plugging agent applied to offshore oilfield high-permeability reservoir based on quantum dots
CN115181217A
Quantum dot light-emitting film, preparation and application of quantum dot light-emitting film in white-light Mini-LED device
CN115247060A
Application of quantum dots in unconventional oil reservoir exploitation, oil-displacing agent and method for increasing yield by using oil-displacing agent
CN115306362A
High-brightness and high-stability water-soluble quantum dot fluorescent microsphere and preparation method thereof
CN117736722A
Temperature-resistant and salt-resistant polymer microsphere and preparation method thereof
CN118580443A